DETECTION OF Î²-THALASSAEMIA TRAIT: ASTI DY OF FIFTY FEMALES - ANJUM, SHAHID; TAQYYAB, MUHAMMD; SHAH, SYED HUMAYUN; CHAUDHRY, NASEER (Journal of Ayub Medical College Abbottabad, 2001)
Background: his study was carried out to detect beta-thalassaemia frail in the siblings of beta thalassaemia major children by Hemoglobin (Hb) electrophoresis Methods: Subjects were divided into two groups Group I Mas the patterns group comprising 100-subjects siblings of beta- thalassaemia major children and Group 2 was the control group with 25-subjects Results: It was observed that 58% of the siblings of beta-thalassaemia major children had betathalassaemia trail Even in the control group 2 subjects had beta thalassaemia trait which shows that thalassaemia gene is very common in Hazara division of Pakistan.